-6+9(x-1)=16x+2-7x

Simple and best practice solution for -6+9(x-1)=16x+2-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+9(x-1)=16x+2-7x equation:


Simplifying
-6 + 9(x + -1) = 16x + 2 + -7x

Reorder the terms:
-6 + 9(-1 + x) = 16x + 2 + -7x
-6 + (-1 * 9 + x * 9) = 16x + 2 + -7x
-6 + (-9 + 9x) = 16x + 2 + -7x

Combine like terms: -6 + -9 = -15
-15 + 9x = 16x + 2 + -7x

Reorder the terms:
-15 + 9x = 2 + 16x + -7x

Combine like terms: 16x + -7x = 9x
-15 + 9x = 2 + 9x

Add '-9x' to each side of the equation.
-15 + 9x + -9x = 2 + 9x + -9x

Combine like terms: 9x + -9x = 0
-15 + 0 = 2 + 9x + -9x
-15 = 2 + 9x + -9x

Combine like terms: 9x + -9x = 0
-15 = 2 + 0
-15 = 2

Solving
-15 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9+2i=0 | | 7(x+4)-3=29-2x-4+9x | | -28=x-3.7 | | 200/x=3x | | 1/4-x=3/x | | (d^3+d^2-4d)y=0 | | 4(b+3)=9 | | 12x+11=156 | | 28y+4x=4 | | -3p/2;0 | | x^2=16y-32 | | 25=18-2y | | -2(5x-9)+7=-10X+25 | | -26=9+5x | | 7x(2)=63 | | (3/5)2 | | 0.25x=(9/365)x | | x^4-12x^3+36x^2-20x+3=0 | | x+(x*.12)=765 | | I-(1+7x)-6(-7-x)=36 | | 15/20=3/x | | 8.3w-w-8.9=1.5 | | -6x-6=10 | | 19/21-2/3 | | 6y+9=2thirdsx | | -6x+3=10 | | X^2-45x+506=0 | | (-2/7)^3 | | [9(n+5)-19]-[3(n-4)+2]= | | -6x-3=10 | | -100a^2-9=0 | | 3x^2-5x+20=0 |

Equations solver categories